1982
DOI: 10.1111/j.1439-0329.1982.tb01391.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of the monoterpene fraction in wounded wood of Picea abies and its significance for the resistance against wound infecting fungi

Abstract: The wood of Picea abies reacts to injuries with an alteration of the terpene fraction in the resin. This fact may play a role in the host-parasite interaction. The significance for resistance against wound infecting fungi is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
11
1
1
Order By: Relevance
“…The increase in total monoterpenes (hydrocarbides) after treatment is in agreement with all previous results of phloem and sapwood reactions in different conifer species (Shrimpton, 1973;Russel and Berryman, 1976;Raffa and Berryman, 1982a, b;Schuck, 1982;Miller et al, 1986;Delorme and Lieutier, 1990 The conclusion that the reaction is nonspecific for the agression supports the results of Cook and Hain (1985), with Loblolly pine and 2 strains of Ophiostoma minus, and of Delorme and Lieutier (1990) with Scots pine and 3 different fungi and 1 beetle species. In his histological studies, Mullick (1977) …”
Section: Comparison Between Treatmentssupporting
confidence: 80%
See 3 more Smart Citations
“…The increase in total monoterpenes (hydrocarbides) after treatment is in agreement with all previous results of phloem and sapwood reactions in different conifer species (Shrimpton, 1973;Russel and Berryman, 1976;Raffa and Berryman, 1982a, b;Schuck, 1982;Miller et al, 1986;Delorme and Lieutier, 1990 The conclusion that the reaction is nonspecific for the agression supports the results of Cook and Hain (1985), with Loblolly pine and 2 strains of Ophiostoma minus, and of Delorme and Lieutier (1990) with Scots pine and 3 different fungi and 1 beetle species. In his histological studies, Mullick (1977) …”
Section: Comparison Between Treatmentssupporting
confidence: 80%
“…This is explained by the fact that reactive sapwood had a composition close to that of unwounded sapwood. Shrimpton (1973) only found an increase in β-phellandrene, which is contrary to our results, but this may be due to betweentree variation in the qualitative response, as observed by Schuck (1982) in the sapwood of P abies and by Delorme and Lieutier (1990) (1988) suggested that the neosynthesis against a beetle-associated fungus in Pinus pinaster is preceded by the reactivation of previously inactive cells.…”
Section: Comparison Between Tissuescontrasting
confidence: 56%
See 2 more Smart Citations
“…Yamada, 1992). The antimicrobial activities of volatile terpenes (Shrimpton & Whitney, 1968;Cobb et al, 1968;Flodin, 1979;Schuck, 1982a) and resin acids (Henricks, Ekman &. von Weissenberg, 1980;Franich, Gadgil & Shain, 1983) have been demonstrated in a number of studies.…”
Section: {A) Environmental Constraints On Pathogen Growthmentioning
confidence: 99%